The Role of Tetrahydrobiopterin and Dihydrobiopterin in Ischemia/Reperfusion Injury When Given at Reperfusion. (26th April 2010) - Chen, Qian; Kim, Elizabeth Eun Jung; Elio, Katrina; Zambrano, Christopher; Krass, Samuel; Teng, Jane Chun-wen; Kay, Helen; Perkins, Kerry-Anne; Pershad, Sailesh; McGraw, Sloane; Emrich, Jeffrey; Adams, Jovan S.; et al.
Abstract : Reduced nitric oxide (NO) bioavailability and increased oxidative stress are major factors mediating ischemia/reperfusion (I/R) injury. Tetrahydrobiopterin (BH 4 ) is an essential cofactor of endothelial NO synthase (eNOS) to produce NO, whereas dihydrobiopterin (BH 2 ) can shift the eNOS product profile from NO to superoxide, which is further converted to hydrogen peroxide (H 2 O 2 ) and cause I/R injury. The effects ofBH 4 andBH 2 on oxidative stress and postreperfused cardiac functions were examined in ex vivo myocardial and in vivo femoral I (20 min)/R (45 min) models. In femoral I/R, BH 4 increased NO and decreasedH 2 O 2 releases relative to saline control, and these effects correlated with improved postreperfused cardiac function. By contrast, BH 2 decreased NO release relative to the saline control, but increasedH 2 O 2 release similar to the saline control, and these effects correlated with compromised postreperfused cardiac function. In conclusion, these results suggest that promoting eNOS coupling to produce NO and decreaseH 2 O 2 may be a key mechanism to restore postreperfused organ function during early reperfusion.